A prospective study comparing the FLIR ONE with laser Doppler imaging in the assessment of burn depth by a tertiary burns unit in the United Kingdom - Jay Goel; Metin Nizamoglu; Alethea Tan; Helen Gerrish; Karen Cranmer; Naguib El-Muttardi; David Barnes; Peter Dziewulski (SAGE Publishing, 2020)
Introduction: Laser Doppler imaging (LDI) is the 'gold standard' tool for the assessment of burn depth. However, it is costly. The FLIR ONE is a novel, mobile-attached, thermal imaging camera used to assess burn wound temperature. This study compares the FLIR ONE and LDI in assessing burn depth and predicting healing times. Methods: Forty-five adult patients with burn wounds, presenting at 1-5 days, were imaged with the FLIR ONE and LDI. Infected, chemical and electrical burns were excluded. Healing potential was determined by comparing wound and normal skin temperature for the FLIR ONE and blood flow changes with the LDI. Healing potential was categorised into wounds healing in less than and over 21 days. Pearson's test was used to determine the correlation between changes in wound temperature and healing potential. Results: Percent total body surface area (%TBSA) was in the range of 0.5-45. FLIR demonstrated a sensitivity of 66.67% and specificity of 76.67% in predicting healing within 21 days, while LDI demonstrated a sensitivity of 93.33% and specificity of 40%. The FLIR ONE showed a significant difference in the mean temperature changes between burns that healed in less than (0.1933 ± 0.3554) and over 21 days (-1 ± 0.4329) ( P = 0.04904). Pearson's test showed a significant correlation between the difference in wound and normal skin temperature with healing times ( P = 0.04517). Conclusion: The inexpensive FLIR ONE shows a significant correlation between changes in wound temperature and healing times. It is useful in predicting healing within 21 days. However, evaporative cooling at the wound surface can lead to overprediction of healing times and overtreatment. Lay Summary Background Laser Doppler imaging is currently the main tool for burn depth assessment. It works by analysing the blood flow in a burn wound. Based on these findings, it can predict the depth of the burn injury and predict if it will heal in less than or over 21 days. The main problem is that it is costly. The FLIR ONE is a novel, mobile-attached, thermal imaging camera. It can be used to assess burn depth by comparing the temperature of the burn wound to the surrounding normal skin. This information can then be used to predict healing times into less than and over 21 days. The issue being explored The usefulness of the FLIR ONE in assessing burn depth and predicting healing time when compared to the LDI. How was the work conducted? Forty-five adult patients who sustained a burn injury within the last five days were imaged with both the FLIR ONE and LDI. Those with infected, electrical or chemical burns were excluded. Healing potential was determined by comparing the temperature of the burn wound with normal skin for the FLIR ONE and by changes in wound blood flow with the LDI. Healing potential was categorised into wounds healing in less than and over 21 days. The correlation between the temperature changes of the burn wound and healing time was evaluated for the FLIR ONE. What we learned from the study This study was able to demonstrate that the FLIR ONE showed a significant correlation between the temperature difference between the burn wound and normal skin with healing times. When compared with the LDI, the FLIR ONE was useful in predicting if a burn wound will heal in less than 21 days. The FLIR ONE has advantages over the LDI, it is low cost, portable and produces instantaneous images. Ultimately, this developing technology may increase access to higher standard burn care in centres where LDI is not affordable.